Anthracycline and taxane containing chemotherapy for early-stage operable breast cancer: meta-analyses of 100,000 women in 86 randomised trials - Braybrooke, J; Gray, R; Bradley, R; Hills, R; Pan, H; Peto, R; Dodwell, D; McGale, P; Taylor, C (Elsevier, 2023)
Background: Anthracycline–taxane chemotherapy for early-stage breast cancer substantially improves survival compared with no chemotherapy. However, concerns about short-term and long-term side-effects of anthracyclines have led to increased use of taxane chemotherapy without anthracycline, which could compromise efficacy. We aimed to better characterise the benefits and risks of including anthracycline, and the comparative benefits of different anthracycline–taxane regimens.